Deposition of Colloidal Titanium Oxide Nanoparticles using Pulsed Nd: YAG Laser Ablation in Liquid to Increase the Efficiency of the Si Solar Cell - Salman, Amenah Ali; Tarik, Hiba S; Yahea, Khaled Z (Al-Nahrain Journal of Science, 2018)
This work reports the attempts to carry out pulsed laser ablation in liquid (PLAL) for synthesizing colloidal Titanium dioxide nanoparticles (NPs). TiO2 NPs was synthesized by 7ns Nd:YAG laser ablation of high purity titanium target (99.99 %) immersed in water ,and deposited the film on silicon solar cell to increase the efficiency of the Si solar cell . The surface morphology of the deposits materials have been studied by using atomic force microscopes (AFM). Atomic Force Microscopy(AFM) analysis showed that the average grain size of TiO2NPsinwater were 150 nm and rms roughness values are (2.27 nm) for TiO2 thin film. The photovoltaic characteristics before and after deposited Titanium dioxide nanoparticles (NPs) included short circuit current (Jsc),open circuit voltage (Voc), where the maximum (Jsc), (Voc)and fill factor (FF) obtained at AM1after deposited were 40.2 (mA cm-2) , 630(mV) and(0.7) respectively. After deposited Titanium dioxide nanoparticles (NPs)increase the efficiency of the Si solar cell13.8 % instead of 10.3% conversion efficiency before the deposited.